Cultural Symbiosis and the Role Of Religion in the Contemporary World: An Islamic Perspective - Bakar, Osman (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The main aim of this paper is to provide an introductory discussion of the issue of the human need for a cultural symbiosis in the contemporary global community and of the constructive role that religion could play in delivering this global need. We will, however, be examining the issue at hand mainly from the perspective of Islam, since it happens to be the religion with which we are most familiar. But our chosen theme of discussion here with an emphasis on Islam is also influenced by other considerations. We realize that the perspective of Islam on the issue in question is little known to many non-Muslims even though it is important in its own right, thus meriting a serious study by scholars. Today, Islam is the second largest religion in the world after Christianity and also the fastest growing. Moreover for various reasons, Islam is increasingly recognized even by its critics as having the capacity to positively influence world events and global affairs and the future direction of world history. More often than not, Islam’s influence is perceived negatively. The association of Islam with violence, as portrayed by many circles today, is a good illustration of this widespread misperception of Islam. In these circumstances, it is therefore important to highlight Islam’s positive teachings drawn from its rather rich treasury – spiritual, intellectual, and cultural – that could give a big helping hand to the present humanity in its task of realizing the goal of cultural symbiosis in this sharply polarized world.